PEDAGOGICAL BASIS OF FORMATION OF MILITARY CULTURE COMPETENCES IN YOUTH - Qahhorov Siyavush Khudayarovich (American Journals, 2023)
The article describes the development of military-patriotic qualities, youth military culture and its specific features in the defense of the Motherland, its national security, territorial integrity and sovereignty. The place and role of mechanisms of military culture in the formation of military culture competences in young people and their upbringing as morally and morally mature people have been researched, and the social and pedagogical issues of military culture have been considered.
Keywords: Culture, youth, military field, defender of the homeland, patriotism, military culture, military duty, human capital.